Mucosal healing of ileal lesions is associated with long‐term clinical remission after infliximab maintenance treatment in patients with Crohn's disease. Issue 1 (17th July 2014) - Beppu, Takahiro; Ono, Yoichiro; Matsui, Toshiyuki; Hirai, Fumihito; Yano, Yutaka; Takatsu, Noritaka; Ninomiya, Kazeo; Tsurumi, Kozue; Sato, Yuho; Takahashi, Haruhiko; Ookado, Yuuki; Koga, Akihiro; et al.
<x xml:space="preserve">Abstract</x> Background and Aim The aim of the present study was to endoscopically evaluate ileal mucosal healing during maintenance therapy with infliximab in order to investigate the clinical significance of endoscopic examination of ileal lesions in Crohn's disease patients. Methods This study retrospectively analyzed 54 patients who mainly had active ulcers of the ileum on endoscopy at baseline who were responsive to infliximab induction and who received infliximab maintenance therapy. Mucosal healing was defined as no ulcer or only ulcer scar. At the time of follow‐up endoscopy after starting infliximab, endoscopic score, mucosal healing, and clinical remission were evaluated. On long‐term follow up, correlations between mucosal healing and long‐term clinical remission, and between mucosal healing and the need for major abdominal surgery, were also evaluated. Results Ileal mucosal healing and complete mucosal healing were significantly correlated with clinical remission (P = 0.046, P = 0.0001, respectively). The rate of long‐term clinical remission was significantly higher in patients with complete mucosal healing (P = 0.025). The rate of major abdominal surgery for strictures was significantly lower in patients with complete mucosal healing (P = 0.044). Conclusions Complete mucosal healing after 1–2 years was a predictive factor for long‐term clinical remission up to 4 years after starting infliximab. A lack of complete mucosal healing was a predictive factor for major abdominal surgery for strictures. The present study suggests that endoscopic evaluation of ileal lesions is useful for long‐term prognosis of Crohn's disease patients.